1989
DOI: 10.1210/mend-3-9-1477
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Placental Aromatase inSaccharomyces cerevisiae

Abstract: A full-length human placental aromatase cDNA clone, Aro 2, was isolated upon screening a human placental cDNA library with an aromatase cDNA probe and an oligonucleotide probe whose sequence was derived from a human aromatase genomic clone. Nucleotide sequence microheterogeneity was found in the 3'-untranslated region among Aro 2 and in two previously described human aromatase cDNA clones. Both the minor sequence differences and the expression of a single protein species in placental tissue suggest the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The translation start site is positioned in exon II and one of the 5 ¶-untranslated exon I's of aromatase mRNA is spliced onto a common splicing junction of exon II, upstream of the translation start site (10)(11)(12). It has been found that the various untranslated exon I's are present at different levels in different aromataseexpressing tissues and cells (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The translation start site is positioned in exon II and one of the 5 ¶-untranslated exon I's of aromatase mRNA is spliced onto a common splicing junction of exon II, upstream of the translation start site (10)(11)(12). It has been found that the various untranslated exon I's are present at different levels in different aromataseexpressing tissues and cells (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Four mutants of human aromatase have been expressed in Chinese hamster ovary cells using a stable expression method. The activities of these mutants were determined using [13, (2)(3)(4)(5) and the inhibition ofthe enzyme as part ofa therapeutic approach to this disease make the study of aromatase of paramount importance. This enzyme is also of interest to a number of investigators (e.g., refs.…”
mentioning
confidence: 99%
“…Although the human placental aromatase cDNA has been cloned and the complete amino acid sequence of the enzyme has been deduced from the nucleotide sequence (10)(11)(12)(13), the structure-function relationship of the enzyme has yet to be established. A mammalian cell expression plasmid, pH P-A~io, containing the human placenta aromatase cDNA, was constructed recently, and this enzyme was expressed in Chinese hamster ovary (CHO) cells by a stable expression method using this plasmid (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of gene engineering techniques have been employed for the high throughput aromatase inhibitor screening kit. Although human CYP19 has been expressed in E.coli [5], yeast [6], and insect cells [7][8][9], only inclusion body was obtained from E.coli expression due to the lack of necessary protein modification system. On the other hand, even if it can be actively expressed in eukaryotic cells, such as yeast and insect cells, the harsh cultivation conditions and low growth rate of the insect cells limit its extensive application for producing aromatase.…”
Section: Introductionmentioning
confidence: 99%